ANALYSIS OF DRIVING SPEED IN HIGHWAY AND PSYCHOLOGICAL FACTORS IN SPEEDING BEHAVIOR IN THE JAKARTA AREA AND ITS SURROUNDINGS (CASE STUDY: BEKASI MAIN STREET) - Guritnaningsih Guritnaningsih; Martha Leni Siregar; Ahmad Septiawan (Journal of Indonesia Road Safety, 2019)
Driving a vehicle above the speed limit is unsafe driving behavior that may cause the occurrence of an accident. Speed limitation can be one way to improve road safety. This study aims to get an illustration of speed limit violation committed by the drivers on the national road segment, and also to investigate the demographic and psychological factors that affect driver behavior in violating the speed limit as stated in the traffic regulation. Speed data collection was carried out at the Bekasi Raya national road in Bekasi, while the demographic and psychological data were collected using questionnaires through online methods. The result of speed measurement using Speed Gun to 30 motorcycles, 30 light vehicles, and 30 heavy vehicles, shows that there are no light or heavy vehicles that drive above the speed limit. Speeding behavior only is indicated by a little number of motorcyclists. From the online survey through the distribution of questionnaires to 102 motorcyclists, it was found that speeding behavior tends to be done when they are in a rush situation. Mengendarai kendaraan di atas batas kecepatan (ngebut) merupakan perilaku mengendara yang berkontribusi terhadap terjadinya kecelakaan..Salah satu cara untuk meningkatkan keselamatan di jalan raya adalah dengan pembatasan kecepatan. Penelitian ini bertujuan untuk mendapatkan gambaran tentang pelanggaran batas kecepatan yang dilakukan pengemudi di ruas jalan nasional, dan faktor-faktor demografis, serta faktor psikologis yang berperan dalam perilaku pengendara kendaraan bermotor melanggar batas kecepatan yang telah ditentukan oleh peraturan lalu lintas. Pengambilan data kecepatan dilakukan di jalan nasional Bekasi raya, sedangkan data tentang faktor demografis dan psikologis diperoleh melalui penyebaran kuesioner melalui online. Hasil pengukuran kecepatan terhadap 30 sepeda motor, 30 kendaraan ringan, dan 30 kendaraan berat dengan Speed Gun menunjukkan bahwa tidak ada kendaraan ringan maupun kendaraan berat yang mengemudikan kendaraan di atas batas kecepatan. Perilaku ngebut dilakukan oleh sebagian kecil pengendara sepeda motor. Dari survey melalui penyebaran kuesioner terhadap 102 pengendara diperoleh gambaran bahwa perilaku ngebut cenderung dilakukan ketika berada pada situasi tergesa-gesa.